CP-190 Incidence and risk factors associated with treatment failure in patients receiving antiretroviral therapy. (14th February 2016) - Retamero, A; Luque, S; Echeverría-Esnal, D; Molas, E; Florit, M; Knobel, H; Gonzalez-Colominas, E; Conde-Estevez, D; Carballo, N; Ferrandez, O
Abstract : Background: Despite current highly active antiretroviral therapy (HAART), some patients still do not achieve an undetectable viral load, and it is important to identify treatment failure (TF) associated factors. Purpose: To determine the incidence and risk factors for TF in a cohort of HIV infected patients. Material and methods: Cross sectional study in an initial cohort of 1562 HIV infected patients from June 2014 to July 2015. 1259 were finally included and interviewed, to collect the following data: demographics, current ART and adherence, concomitant medications and drug interactions (DI) (according to the University of Liverpool database). TF was defined as confirmed HIV RNA >50 copies/mL. A logistic regression analysis was used to identify variables independently related to TF. Results: Patients included: 1259 (80.6%); patients excluded: 303 (19.4%) due to lack of data or lost to follow-up. Univariate analysis: Patients with and without TF: 151 (12.0%) versus 1108 (88.0%), male (82.1% vs 80.1%, p = 0.587), age (42.9 vs 48.0 years, p < 0.001), Caucasian (75.5% vs 81.9%, p = 0.060), smokers (61.7% vs 51.3%, p = 0.018), alcohol consumption (47.7% vs 28.3%, p < 0.001), drug users (30.9% vs 12.4%, p < 0.001), CD4 + T cell count (526.0 vs 716.3 cells/µL, p < 0.001), hepatitis B (6.6% vs 5.2%, p = 0.664) and hepatitis C virus (33.8% vs 29.9%, p = 0.548). HAART: non-nucleoside/nucleotide reverse transcriptase inhibitors (NNRTI) (35.8% vs 55.0%, p < 0.001), protease inhibitors (52.3% vs 39.7%, p = 0.004) and integrase inhibitors (19.9% vs 13.8%, p = 0.064). Adherence <90%: 45 (29.8%) versus >90 (8.1%), p < 0.001; patients with other medications (107 (70.9%) vs 774 (69.9%), p = 0.757), with a DI (72 (47.7%) vs 493 (44.5%), p = 0.460) and a contraindicated DI (2 (1.3%) vs 39 (3.5%), p = 0.219). Goodness-of-fit: Hosmer and Lemershow test (p = 0.889). Discriminative ability: AUC 0.744 (95% 0.702 to 0.787), p < 0.001. Conclusion: Risk factors related to treatment failure were younger age, alcohol or drug use, poor adherence and use of HAART not including an NNRTI. Despite advances in HIV treatment, poor adherence is still the most important factor for treatment failure and justifies the need for multidisciplinary management of these high risk patients. No conflict of interest.